La Situation des langues classiques dans l'enseignement francais (The Status of Classical Languages in French Schools) - Schilling, Robert; Joint Association of Classical Teachers, Oxford (England). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1963)
A review of the status of classical studies in France reveals a serious decline in enrollment in Greek classes. The essential problem in curricular planning is seen as the need to find an equilibrium between culture and technology since Latin is seen as the key to the culture of the Western world. Criticism of teaching methods and theory is directed toward programs in which classical studies tend to become studies in philology. (RL)
Didaskalos, v1 n1 p37-44 1963.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classical Literature; Cultural Background; Cultural Education; Educational Problems; Greek; Greek Civilization; Language Instruction; Language Programs; Latin; National Surveys; Second Language Learning; Teaching Methods; Western Civilization; France